PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI MENGGUNAKAN APLIKASI CAPCUT PADA MUATAN IPS DIKELAS V SDN 44/VIII TELUK SINGKAWANG KABUPATEN TEBO - Yulia Darniyanti; Muhammad Subhan; Vinni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problems in this study were caused by monotonous and passive learning activities that made students feel bored and less interested. Teachers also often use the old way of learning, such as only using worksheets in learning activities. Based on the problems above, there is still a need for improvement in the learning process for students to improve learning outcomes, namely by using an animation video media using the CapCut application in teaching. The purpose of this study was to develop animated video learning media using the CapCut application for social studies content in class V. This type of research used for this type of research is Research and Development (R&D). The ADDIE model has 5 parts that are interconnected with the others, namely: Analyze ( Analysis), Design (Design), Development (Development), Implementation (Implementation), Evaluation (Evaluation). The type of data used in this research is quantitative and qualitative data. The instruments used are validity, practicality and effectiveness. Data collection techniques used interviews, observation and documentation. The analysis technique used is validity, practicality and effectiveness analysis. Based on that the learning outcomes of students have reached KKM 70 Completeness, the learning outcomes of students with an average of 85.5% are categorized as very effective because the animated video has provided results that are in accordance with the learning objectives based on the results of student learning tests. Meanwhile, the incompleteness of students with an average of 12.5% ​​is categorized as ineffective because the test results during the trial showed that students did not meet the minimum completeness. So that animated videos can be applied in the learning process.